The pathology associated with diabetic retinopathy. (October 2017) - Lechner, Judith; O'Leary, Olivia E.; Stitt, Alan W.
Abstract: This review summarizes the pathological features of diabetic retinopathy. The lesions occurring in the diabetic retina have been described over many decades using descriptive and experimental approaches based on clinical studies on patients, human post-mortem material, animal models and various in vitro systems. We have also accumulated a wealth of knowledge about basic molecular mechanisms and key pathogenic processes that drive these abnormalities in diabetic retina. Despite these advances, there are still limited therapeutic options for diabetic retinopathy with those currently available only addressing late-stage disease. With a particular focus on the earlier stages of diabetes, there is growing appreciation the complex neuronal, glial and microvascular abnormalities which progressively disrupt retinal function. This is especially true from the perspective of the neurovascular unit during health and disease. Based on a strong appreciation of cellular and molecular pathology that underpins diabetic retinopathy, further advances are anticipated as we drive towards development of efficacious therapeutic options that can address all stages of disease.